Climate-driven environmental changes around 8,200 years ago favoured increases in cetacean strandings and Mediterranean hunter-gatherers exploited them - Mannino, Marcello A. (Sci Rep, 2015)
Cetacean mass strandings occur regularly worldwide, yet the compounded effects of natural and anthropogenic factors often complicate our understanding of these phenomena. Evidence of past stranding episodes may, thus, be essential to establish the potential influence of climate change. Investigations on bones from the site of Grotta dell’Uzzo in North West Sicily (Italy) show that the rapid climate change around 8,200 years ago coincided with increased strandings in the Mediterranean Sea. Stable isotope analyses on collagen from a large sample of remains recovered at this cave indicate that Mesolithic hunter-gatherers relied little on marine resources. A human and a red fox dating to the 8.2-kyr-BP climatic event, however, acquired at least one third of their protein from cetaceans. Numerous carcasses should have been available annually, for at least a decade, to obtain these proportions of meat. Our findings imply that climate-driven environmental changes, caused by global warming, may represent a serious threat to cetaceans in the near future.